THE FEASIBILITY STUDY ANALYSIS OF FOOD BUSINESS DEVELOPMENT - Dadang Krisdianto; Afham Gulwani; Arif Rahman; Azhar Ahmad; Muhamad Rafly; Mochammad Ferdian Maulana; Reyzales Setiawan (Universitas Islam Malang, 2023)
The purpose of this study is to determine the feasibility of business development business at CV Yeyen Catering. This study uses 7 main aspects that are used in analyzing business feasibility and the results show that all of these aspects indicate this business development plan in terms of legal, market and marketing, financial, technical and operational, management, social and economic aspects, as well as environmental impact aspects. . The research method used in this study is qualitative and quantitative with data collection techniques field observations, interviews, and literature review. The results of the research show that the feasibility of this company is quite good and feasible to be developed.